Slow pyrolysis characteristics of bamboo subfamily evaluated through kinetics and evolved gases analysis. (October 2019) - Zhao, Rongxuan; Wang, Xin; Liu, Liansheng; Li, Pei; Tian, Liang
Highlights: Bamboo subfamily was subjected to pyrolysis conducted by TG-FTIR analyses. Thermodynamic parameters and kinetics of bamboo subfamily pyrolysis were elucidated. Average activation energy was 201.59, 220.49, and 224.47 kJ/mol respectively. FTIR curves can be divided into three fitted curves based on key components in bamboo. Abstract: The objective of this study is to investigate the pyrolysis and kinetic characteristics of three varieties of the bamboo subfamily via thermogravimetry/Fourier transform infrared spectrometry (TG-FTIR) coupling technologies. The pyrolysis process can be divided into three stages of dehydration, volatilization, and carbonization. TG-FTIR analysis revealed that evolved gas is constituted by CO2, CO, CH4, H2 O, NO, NO2, formic acid, HCN, and CO functional groups as major pyrolysis products. The kinetic parameters of pyrolysis were calculated using model-free methods of distributed activation energy (DAEM). With an increase in conversion, the activation energy of each bamboo subfamily exhibited distinct variations. The average values of activation energy for moso bamboo, bambusa multiplex, and black bamboo determined by DAEM were 201.59, 220.49, and 224.47 kJ/mol, respectively. Results of thermodynamic and kinetic analysis indicate that the bamboo subfamily shows great potential as an alternative fuel by pyrolysis.